86 Long term clinical outcomes in patients requiring cardiac pacing due to congenital complete heart block. (6th June 2022) - Seitler, Sam; Behar, Jonathan
Abstract : Background: Isolated congenital complete heart block (CCHB) is rare cardiac condition associated with maternal Anti-Rho antibodies. It is managed with permanent pacemaker insertion. We sought to determine the long-term outcomes of individuals with CCHB who had undergone pacemaker insertion. Methods: A database search was performed at a UK tertiary cardiac referral centre. The online medical records of patients with CCHB were analysed for pacing requirements and complications, echocardiographic data, and clinical status. Results: A total of 72 patients (female n = 46) were identified, 20% of whom were autoantibody positive. Mean age of initial implantation was 15.5 years (SD 12.7) with mean follow up of 21 years (SD 8.3). 88% of patients were NYHA class I at censure of data. Major adverse cardiac events (MACE) were observed in 2 patients with 0% mortality throughout the follow up period. 10 patients (13.9%) developed cardiomyopathy. Five patients had device related infections and 7 required system extractions. Mean left ventricular ejection fraction on most recent echocardiogram was 53.7% (SD 8.40) with no significant change compared with their historic scan. Mild tricuspid regurgitation was the most frequently observed valvular pathology, identified in 28% of patients. Only 2 patients (2.7%) had severe valve incompetence. Conclusion: Long-term outcomes for patients with congenital complete heart block who undergo pacemaker insertion are highly favourable. Despite high pacing requirements over an extended period, the incidence of MACE and pacing related complications is low. Cardiac function and valvular competence are largely preserved but dilated cardiomyopathy remains a late complication. Conflict of Interest: Nil